CURRICULAR POLICIES IN THE TEACHING OF HISTORY IN BASIC EDUCATION BASED ON ICT - Soares, Kauan Pessanha; Pedrosa, Stella Maria Peixoto de Azevedo (Seven Editora, 2025)
The dissemination of digital technologies has significantly transformed learning spaces and practices, expanding methodologies and tools available for teaching. In schools, these changes have affected both administrative management and pedagogical mediation. However, integrating Digital Information and Communication Technologies (DICT) into History teaching in Basic Education is not a simple task, as it depends on internal factors (infrastructure, access to devices, and technical skills) and external ones (public policies, curricula, and social demands). This paper analyzes how three official documents — the National Curriculum Parameters (1997/1998), the National Curriculum Guidelines for Basic Education (2013), and the National Common Core Curriculum (2017) — address the use of DICT in History teaching, discussing the potential and limitations of their inclusion. The study shows that, although progress has been made in recognizing digital technologies as part of the educational process, challenges remain regarding practical implementation, teacher training, and inequalities in access.DOI: https://doi.org/10.56238/sevened2025.038-062